Physical, Chemical, and Functional Characteristics of Composite Flours from Banana Corm and Tempeh - Sumanti, Debby Moody; Hanidah, In-In; Abdullatif, Muhammad Aziz (Department of Agro-industrial Technology, University of Brawijaya, 2022)
AbstractThis study aimed to determine composite flour's physical, chemical, and functional properties from Sumedang Roid banana corm and tempeh. The sample consisted of five different treatments with ratios of banana corm flour to tempeh flour 100:0, 0:100, 80:20, 70:30, and 60:40. The research data were analyzed using a Randomized Block Design and the Duncan Multiple Range Test (DMRT) at 5% level. Parameters observed included bulk density, color degree, ash content, moisture content, carbohydrate content, fat content, protein content, and pasting properties. The results showed that composite flour with a ratio of banana corm flour to tempeh flour of 60:40 could produce the best composite flour characteristics with a bulk density of 0.44 g/ml, color degree L* 67.86, a* 5.64 and b* 23.34, 5.47% ash content, 8.66% moisture content, 57.60% carbohydrates content, 10.62% fat content, 17.64% protein content, pasting temperature 80.86 °C, peak viscosity 1,265.33 cP, hold viscosity 858.00 cP, final viscosity 1,109.00 cP, breakdown viscosity 407.33 cP, setback viscosity 251.0 cP. The produced composite flour is suitable to be applied on biscuits, cookies, and semi-moist cakes.Keywords: banana stem, composite, flour, Roid banana, tempeh AbstrakPenelitian bertujuan untuk mengetahui sifat fisik, kimia, dan fungsional tepung komposit dari bonggol pisang Roid asal Sumedang dan tempe. Sampel terdiri lima perlakuan berbeda dengan rasio perbandingan tepung bonggol pisang dengan tepung tempe adalah 100: 0, 0:100, 80:20, 70:30, dan 60:40. Data hasil penelitian dianalisis dengan Rancangan Acak Kelompok dan uji lanjutan Duncan Multiple Range Test (DMRT) pada taraf 5%. Parameter pengamatan meliputi densitas kamba, derajat warna, kadar abu, kadar air, kadar karbohidrat, kadar lemak, kadar protein, dan karakteristik pasting. Hasil penelitian menunjukkan bahwa tepung komposit dengan rasio tepung bonggol pisang dengan tepung tempe 60 : 40 mampu menghasilkan karakteristik tepung komposit terbaik dengan densitas kamba 0,44 g/ml, derajat warna L* 67,86, a* 5,64 dan b* 23,34, kadar abu 5.47%, kadar air 8,66%, kadar karbohidrat 57,60%, lemak 10,62%, protein 17,64%, pasting temperature 80,86 °C, peak viscosity 1265,33 cP, hold viscosity 858,00 cP, final viscosity 1.109,00 cP, breakdown viscosity 407,33 cP, setback viscosity 251,0 cP. Tepung komposit yang dihasilkan tersebut sesuai untuk diaplikasikan pada produk biskuit, kukis, dan kue semi basah.Kata kunci: bonggol pisang, komposit, pisang Roid, tempe, tepung